Sakinamah as a Poetic Form of Divan Literature: Sakinamah of Zekeriya Sukkeri - Gačanin, Sabaheta (Prilozi za orijentalnu filologiju, 2017)
This paper gives a brief survey of the historical development of the “sakinamah” poetic genre, primarily of the sufi origin sakinamah. Sakinamah originates from the Persian literary tradition, where it reached its full form and content, and as such was taken over into the Ottoman literary tradition, to which the Bosniak authors in Oriental languages belong, too. Among the preserved divan manuscripts of Bosniak authors, Divan by Zekeriya Sukkeri stands out with a sakinamah in Persian, whose translation has been presented in this paper as an example of this popular genre in literary tradition. Sukkeri’s Sakinama has ali the elements of the mystic content (the sit-together, inn-keeper, glass, wine, drunkenness) as characteristic terms of this literary genre, which gives the poem a certain stereotype, but, despite this, with its comparatively simple language, powerful and suggestible images, it incites an extraordinary. visualisation in the reader.